Integrating Classroom-Based Negotiation Into a Syllabus A Multicycle Action Research Study - Prior, Jemma (bu,press, 2023)
This action research (AR) study concerns an English for Specific Academic Purposes (ESAP) course taught to undergraduate economics students at the Free University of Bozen-Bolzano, a trilingual university in Italy whose degree programmes are taught in German, Italian and English. Despite English for Specific Purposes being an approach to address learner needs, no accurate needs analysis had been conducted. Therefore this study instituted a wide-ranging needs analysis and from the data collected a new learner-centred syllabus was developed for the ESAP course that blended elements from both a product and process approach to syllabus design using classroom negotiation to foster productive skills.